KINERJA GURU IPA TERPADU DI SMP NEGERI 2 SATU ATAP KEPENUHAN HULU DITINJAU DARI PERSEPSI TEMAN SEJAWAT DAN SISWA TAHUN PEMBELAJARAN 2015/ 2016 - Riyanti, Desmi (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
Teacher performance is the level of success of a person or group in carrying out their duties and responsibilities as well as the ability to achieve goalsand standars that have been set. This study aims to determine theperformance of teacher scienseÂ  in SMP N 2 Satu Atap Kepenuhan Hulu judging from peers and students perceptions. This research is descriftive. Population in this research is teacher sciense, teacher not sciense and studentsâ SMP N 2 Satu Atap Kepenuhan Hulu and technik at collage sample use technik total sampling and purposive sampling. Based on the research and analysis which hasbeen done coord conclude that teacher performance sciense in SMP N 2 Satu Atap Kepenuhan Hulu as 80,31% with very good criteria.